Maintaining the Quality of Kacang Buck Semen in Chilled Storage with the Addition of Green Tea Extract in Extender - S. Susilowati; I. Mustofa; W. Wurlina; T. Hernawati; Y. Oktanella (Faculty of Animal Science, Bogor Agricultural University, 2021)
Kacang goats can be bred through artificial insemination techniques using liquid semen from a superior buck. The study was aimed to determine the quality of Kacang buck semen in chilled storage when green tea extract (GTE) was added to the semen extender. Specifically, 12 ejaculates from three Kacang bucks were diluted in skim milk–egg yolk extender containing 0 mg, 0.05, 0.10, and 0.15 mg of GTE/100 mL. The extended semen was stored at 5°C, and its quality was evaluated daily for 5 d. Comparatively, semen with 0.10 mg of GTE/100 mL had the best quality (p<0.05): it had the highest sperm viability, sperm progressive motility, and sperm intact plasma membrane values, and the lowest malondialdehyde levels and DNA fragmentation percentage. However, as the storage period increased, there was a decrease in sperm viability, sperm motility, and sperm intact plasma membrane values with an increase in malondialdehyde levels and DNA fragmentation (p<0.05). The sperm motility of semen with 0.10 mg of GTE/100 mL was maintained during 5 d of chilled storage to meet the qualification for artificial insemination. In contrast, the sperm motility of semen with 0.05 mg and 0.15 mg of GTE/100 mL was maintained for 4 d, whereas that of the control semen was maintained only for 3 d. Thus, the addition 0.10 mg of GTE/100 mL of skim milk-egg yolk extender seems to help maintain the quality of Kacang goat sperm in chilled storage.